Referentes Legales y Orientaciones Pedagógicas Para la Educación Intercultural: Desafíos, Imaginarios y Realidades: Legal Referents and Pedagogical Orientations for Intercultural Education: Challenges, Imaginaries and Realities - De La Hoz Linso, Linda Tivisay; Blanco Díaz, Rubís Mercedes; Caicedo Manjarrez, Cielo Rocío (Universidad del Zulia, 2021)
This article analyzes the legal references and pedagogical guidelines for intercultural education, based on imaginary and realities that emerge in socio-educational contexts. Its methodological approach was developed from a documentary design and bibliographic character, by the theoretical approach that allows the interdisciplinary understanding of the categories of analysis under study. Among the findings, the little correspondence between what is stipulated in the legal references, pedagogical orientations and curricular guidelines and the praxis evidenced in the socio-educational context from the dynamics of intercultural education is revealed.